Pengaruh Era Digital 4.0, Pencarian Produk terhadap Minat Pembelian Produk Melalui Online - Yanto Yanto; Martinus Buulolo; Dedi Susanto (Journal on Education, 2023)
Today's society is in an all-digital condition, but the more sophisticated the renewal and development of the digital revolution will provide positive and negative sides, this is by shopping through online sites it is necessary to be vigilant and must conduct a search for legitimacy before making a purchase action. This research is focused on users of the digital era in industry 4.0, product search, and interest in buying products online. The aim of the research is to analyze the effect of the digital era 4.0, product search on interest in buying products online. The method used is descriptive quantitative with google form. The research informants totaled 26 students of Accounting for Small and Medium Enterprises at the Dharma Bhakti Bangka Community Academy. The results showed that the digital era 4.0 had no positive effect, and was not significant at the error level, product search had a positive and significant effect, another finding that simultaneously had a positive and significant effect on the dependent variable.